THE IMPLEMENTATION OF THE JIGSAW II IN ADOLESCENT REPRODUCTIVE HEALTH EDUCATION OF XI SENIOR HIGH SCHOOL STUDENTS IN GROBOGAN - Nurya Kumalasari; Nurul Kodiyah; Sri Untari (Lppm Unan, 2022)
Background : Specific strategies are needed to increase motivation, knowledge and perception of behavior in health education goals towards learning. Cooperative learning is a learning model in small groups that have different skills. Each member cooperates and helps each other in completing group assignments in order to understand a learning material (Aris, 2014). In this study, a cooperative learning model with the type of jigsaw II which aims to create a learning atmosphere that requires participants to be active in groups and stimulates an active learning atmosphere so that participants feel interested in participating in health education. Research objective : To analyze the effect of the jigsaw in reproductive health education on the knowledge of the eleventh senior high school students. Method: This study used a one-group quasi-experimental pretest-posttest design. The design form used is time series design. The number of samples is 85 respondents. Results : There is an effect of applying the jigsaw II to the level of knowledge with a p-value of 0.000; after health education Conclusion : the jigsaw II is able to provide increased knowledge about reproductive health and feels more enjoyable.